EFEKTIVITAS PEMBELAJARAN ENTREPRENEURSHIP DAN SEMINAR MOTIVASI UNTUK MENINGKATKAN MINAT MENJADI ENTREPRENEUR - Afridayani Afridayani; Syamsul Mu’arif (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
The purpose of this research is to find out 1.) Whether Entrepreneurship Learning has an effect on Increasing Interest in Entrepreneurship, 2.) Is it a Motivation Seminar to Increase Interest in Entrepreneurship 3.) Does Entrepreneurship Learning and Motivation Seminar to Increase Interest in Entrepreneurship. This research method uses a quantitative approach. The research method uses primary data to determine the variables of Entrepreneurship Learning and Motivation Seminar which can increase interest in becoming Entrepreneurship. The quantitative approach is used to examine a specific population or sample. The method used in sampling in this study is non-probability sampling using convenience sampling techniques. Data collection techniques use the questionnaire method, library research (Library Research), quantitative or statistical data analysis with the aim of testing the established hypothesis. Based on the research results, it shows that, 1) Entrepreneurship Learning has an effect on the Increased Interest of Being Entrepreneurship, 2) Motivation Seminar has an effect on Increasing Interest in Becoming Entrepreneurship, 3) Entrepreneurship Learning and Motivation Seminars have an effect on the Increased Interest of Being Entrepreneurship.